Implementasi Algoritma Base64 Sebagai Tingkat Keamanan Data Pada Website Sistem Informasi Pencatat Barang - Tio Lovian; Iskandar Fitri (STMIK Budi Darma, 2022)
The slowness of a job can be affected by many things, mostly due to the large number of files for a single activity. The introduction of a computerized goods recording system is intended to assist users in carrying out their work and facilitate users in finding information on incoming and outgoing goods data. The application made has additional features from previous research, namely exporting incoming and outgoing goods data in the form of 3D graphics and there is a live chat that functions for interaction between application users. For data security, the transaction id stored in the database uses base64 encryption, aiming to secure data from irresponsible parties. In the encryption process, it has been tested using 300 data and has a file size of 1MiB (Mebibyte) by making the data safe and cannot be cracked by other parties. In testing the attack on encrypted data in this application, 20 methods of attack were proven to be unhackable, unless using the encode that was made in this application. The data security process used is to encrypt the transaction id of incoming goods and outgoing goods stored in the database and the description results are found on the website page